Creditor Protection and Credit Response to Shocks - Galindo, Arturo José; Alejandro Micco (World Bank, 2012)
Creditor Protection and Credit Response to Shocks Arturo Jose Galindo and Alejandro Micco This article studies the relationship between creditor protection and credit responses to macroeconomic shocks. Using a data set on legal determinants of finance in a panel of data on aggregate credit growth for 79 countries during 1990 2004, it is shown that credit is more responsive to external shocks in countries with weak legal creditor protection and weak enforcement. The results are statistically and economically significant and robust to alternative measures of creditor protection, to the inclusion of variables that reflect different stages of economic development, to the restriction of the sample to only developing economies, to the controls for systemic crises, to alternative shock measures, and to vector autoregressive specifications. One strand of the literature has shown that an institutional setup that adequately protects creditor rights (CR) can align the incentives of debtors and lenders, increase the expected payoffs of lending, and deepen financial markets. Source: Authors' analysis is based on the data noted in table A-1. Panel a shows how the development of credit markets (as measured by the ratio of credit to the private sector supplied by the financial sector to GDP) is strongly related to a measure of legal protection to creditors: an index of effective creditor rights (ECR) protection that combines legal protection to creditors and their enforcement (higher values indicate stronger protection). Panel data on aggregate credit growth for 79 countries during 1990 2004 support the claim that better legal protections significantly reduce the sensitivity of credit to shocks. Rather than exploring the impact of shocks on output under different scenarios of financial development, it explores the impact of shocks on financial markets, under different institutional setups. Controlling For Systemic Banking Crises And Financial Liberalization Dependent variable: D log(Credit/GDP) (1) External shock External shock* ECR External shock* CL External shock* developed Systemic crisis dummy variable Financial liberalization 1 Financial liberalization 2 Number of observations Number of countries Country-fixed effects Year-fixed effects R-squared Sample 5.656 (1.395)*** 0.665 (0.229)*** -- 21.035 (1.824) 20.062 (0.016)*** -- -- 1.022 79 Yes Yes 0.16 (2) 6.804 (1.663)*** -- 23.198 These results are robust to alternative measures of creditor protection, to the inclusion of variables that reflect different stages of economic development, to the restriction of the sample to developing economies, to controlling for systemic crises and financial liberalization, to alternative shock measures, to possible asymmetric responses, and to vector autoregression dynamic specifications.